Female Auditor and Audit Quality Based on Internal Audit Capability Model (IACM) in the Public Sector - Rida Perwita Sari; Sri Hastuti; Oryza Tannar (Journal of Economics, Business, and Government Challenges, 2020)
The purpose of this study is to examine the influence of competence, Independence and Pressure of Obedience to Audit Quality based on Internal Audit Capability Model (IACM). This research contributes the theoretical and practical benefits as the form of adoption of agency theory and attribution theory and suggestions to improve the expertise of female auditors by taking into account the competence, independence, and pressure of obedience to produce quality inspection in the field of supervision. This study uses a quantitative approach. The analysis technique used in this research is Partial Least Square (PLS) with the help of warpPLS software. The subject of this study is the Inspectorate of East Java Province with a sample of female auditors in the Inspectorate of East Java Province which amounted to 30 female auditors. The results of this study indicate that competence affects the Audit Quality based on Internal Audit Capability Model (IACM), while the independence and pressure of obedience do not effect the Audit Quality based on Internal Audit Capability Model (IACM).